Adaptation of language models via text augmentation - Prachaseree, Chaiyasait (Nanyang Technological University, 2023)
This research aims to adapt a language model to a specific domain using text augmentation techniques. A robust language model requires a lot of domain-specific texts. This thesis focuses on text augmentation to circumvent limited data and domain mismatch. It aims to increase the amount and diversity of training texts by introducing variations of sentences that may be missing in the training corpus.